Pengaruh Tax Avoidance, Multinationality, dan Profitability terhadap Keputusan Perusahaan Melakukan Transfer Pricing - Oktagiari Dwi Putri; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This research aimed to examine the effect of tax avoidance, multinationality, and profitability on transfer pricing. The population in this research are all sektor energy companies listed on the Stock Exchange in 2019-2021. The sampling technique used the purposive sampling. Totality sample are 19 companies. The statistical method use multiple linear regression analysis. The result showed that tax avoidance affects the transfer pricing, while multinationality and profitability does not affect the transfer pricing.